Penerapan Model Roleplaying Pada Materi Rantai Makanan Dalam Meningkatkan Hasil Belajar Peserta Didik: The Application of the Role-Playing Model to Food Chain Material to Improve Student Learning Outcomes - Patra Aghtiar Rakhman; Septiana Dwi Cahyani; Khafidz Aldy Fanani (Sumule Indonesia Publishing, 2024)
Based on the results of observations, it shows that the results of studying science and technology on food chain material for class V students at SDN Kembangan Utara 08 Petang. are still low. Most experience difficulties in achieving the minimum completion criteria (KKM) score. The causal factor is monotonous learning. Educators only use lectures in delivering learning material. Therefore, researchers are trying to make improvements by implementing a roleplaying model which is expected to help in completing science learning. This research method uses a quantitative descriptive approach. The type of research is pre-experimental, which only involves one sample class, namely the experimental class, without a comparison class. Learning outcomes in science and science subjects using the roleplaying model for class V students at SDN Kembangan Utara 08 Petang. have increased. In cycle I the average student score was 75.78571 and in cycle II the average student score was 80.55556, an increase of 4.76985 for the average student score in food chain material. And with the roleplaying model, science and science learning can be carried out completely with good learning results. It can be concluded that the application of the roleplaying model can improve the science and science learning outcomes of class V students at SDN Kembangan Utara 08 Petang.